1985
DOI: 10.1161/01.hyp.7.3_pt_2.i145
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system mediation of acute cardiovascular actions of gamma 2-melanocyte-stimulating hormone.

Abstract: SUMMARY Peptides of the pro-opiocortin class produce pronounced cardiovascular and natriuretic actions. We have investigated the acute cardiovascular effects of one of the most potent members of this class, y 2 -melanocyte stimulating hormone (y 2 -MSH), in rats. Pressor actions of y 2 -MSH administered systemicaMy were eliminated by ganglionic blockade with chlorisondamine. Peripheral cholinergic blockade failed to affect either the pressor or cardioaccelerator responses to y 2 -MSH. Administration of y r MSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…This suggests that the baroreceptor re¯ex-mediated reduction of tonic sympathetic activity due to pressor e ects is inhibited by these peptides. This agrees with ®ndings of Callahan et al (1985;, who reported that the pressor response to g 2 -MSH in conscious rats was blocked by the ganglionic blocking agent chlorisondamine or by blockade of the catecholamine release from sympathetic nerve terminals with bretylium tosylate. Others showed that pressor responses to Arg-Phe containing peptides in anaesthetized rats was reduced by the ganglionic blocking agent hexamethonium (Barnard & Dockray, 1984b).…”
Section: Inhibition Of the Baroreceptoreflexsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the baroreceptor re¯ex-mediated reduction of tonic sympathetic activity due to pressor e ects is inhibited by these peptides. This agrees with ®ndings of Callahan et al (1985;, who reported that the pressor response to g 2 -MSH in conscious rats was blocked by the ganglionic blocking agent chlorisondamine or by blockade of the catecholamine release from sympathetic nerve terminals with bretylium tosylate. Others showed that pressor responses to Arg-Phe containing peptides in anaesthetized rats was reduced by the ganglionic blocking agent hexamethonium (Barnard & Dockray, 1984b).…”
Section: Inhibition Of the Baroreceptoreflexsupporting
confidence: 92%
“…In addition to their e ects on the hormonal system, behaviour, temperature and feeding regulation, g-MSHs and in particular g 2 -MSH and its shorter fragment g 2 -MSH(6 ± 12) have strong e ects on the cardiovascular system (Callahan et al, 1985;Li et al, 1996;Sun et al, 1992;Van Bergen et al, 1995;1997a). Systemic administration of g 2 -MSH and g 2 -MSH(6 ± 12) to rats causes a dose-dependent increase in mean arterial pressure (MAP) and heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%
“…SHU9005 is a novel, potent antagonist of the cloned, transfected rat MC3-R (pA 2 , 8.6) and a full agonist at the cloned human MC4-R (EC50, 4.7 ϫ 10 Ϫ10 M; Kesterson and Cone, unpublished observations). In agreement with published findings (Callahan et al, 1985), the ␣ 1 -adrenergic receptor antagonist prazosin, 0.1 mg/kg intravenously, inhibited the pressor response, whereas the ␤-blocker propranolol, 1 mg/kg intravenously, inhibited the tachycardia elicited by ␥-MSH (data not shown).…”
Section: Centrally Mediated Pressor and Tachycardic Effects Of ␥-Mshsupporting
confidence: 92%
“…In contrast to the cardiovascular depressor effects elicited in the DVC, intravenous injection of higher doses of MSH peptides has been reported to cause pressor and tachycardic effects (Callahan et al, 1985;1988;Gruber and Callahan, 1989;Sun et al, 1992;De Wildt et al, 1993). Indeed, intravenous injection of melanocortins or some of their analogs was found to improve survival in experimental hemorrhagic shock (Bertolini et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation